Feasibility study of high harmonic generation from short wavelength lasers interacting with solid targets - Chambers, D; Norreys, P; Dangor, A; Marjoribanks, R; Moustaizis, S; Neely, D; Preston, S; Wark, J; Watts, I; Zepf, M (1998)
The generation of the third and fourth harmonics from the interaction of a 1 ps, ultraviolet (UV), krypton fluoride (KrF) laser with a solid surface is investigated. The conversion efficiency is seen to increase linearly with Iλ2, with a transition from specular harmonic emission to emission into 2π steradians occurring between 1015 and 1016 W cm-2 μm2. The diffuse emission is strongly dependent on the incidence angle of the laser, with the peak in emission at around 30° being consistent with measurements for resonance absorption. Finally, the conversion efficiencies are found to be in agreement with particle-in-cell (PIC) simulations including appropriate density scalelengths. © 1998 Elsevier Science B.V.